2005
DOI: 10.1177/153476560501100206
|View full text |Cite
|
Sign up to set email alerts
|

Stockholm Effects and Psychological Responses to Captivity in Hostages Held by Suicide Terrorists.

Abstract: October 2002, 800 plus hostages were held for three days in a Moscow theater by suicide terrorists armed with bombs. The stand-off ended when Russian Special Forces gassed and stormed the theater. One hundred thirty of the hostages died. The authors - an American psychologist and colleagues from the Russian Academy of Sciences - began to collaborate soon after the event. This article reports on interviews with eleven hostages regarding their psychological responses to captivity including their expressions of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 12 publications
(11 reference statements)
0
9
0
Order By: Relevance
“…Favaro et al found that an increased number of humiliating or depriving experiences is associated with evidence of Stockholm syndrome among victims. Furthermore, half of the victims ( n = 12) in Favaro et al's sample developed a positive bond with their captors (Favaro et al, 2000 ), whereas Speckhard et al ( 2005a ) found evidence of Stockholm syndrome in 91 % ( n = 10) of their sample of hostage victims.…”
Section: Chaptermentioning
confidence: 92%
See 2 more Smart Citations
“…Favaro et al found that an increased number of humiliating or depriving experiences is associated with evidence of Stockholm syndrome among victims. Furthermore, half of the victims ( n = 12) in Favaro et al's sample developed a positive bond with their captors (Favaro et al, 2000 ), whereas Speckhard et al ( 2005a ) found evidence of Stockholm syndrome in 91 % ( n = 10) of their sample of hostage victims.…”
Section: Chaptermentioning
confidence: 92%
“…In addition, Jameson ( 2010 ) argued that Stockholm syndrome "has little basis in contemporary authorized psychological knowledge" (p. 339), and Namnyak and colleagues noted that Stockholm syndrome does not exist in any of the formal diagnostic classifi cation systems, such as the Diagnostic and Statistical Manual of Mental Disorders ( DSM-IV-TR ; American Psychiatric Association [APA], 2000 ). Nevertheless, what little empirical research that does exist has generally supported academic theoretical depictions of the phenomenon (e.g., Auerbach, Kiesler, Strentz, Schmidt, & Serio, 1994 ;, and fi ndings have confi rmed the presence of Stockholm syndrome in some hostages post-captivity (e.g., Favaro, Degortes, Colombo, & Santonastaso, 2000 ;Speckhard, Tarabrina, Krasnov, & Mufel, 2005a, 2005bWesselius & DeSarno, 1983 ).…”
Section: Chaptermentioning
confidence: 99%
See 1 more Smart Citation
“…This is something important to keep in mind for those who hope to intervene positively in a suicidal terrorism standoff, that the hostages and terrorists have very likely created some bonds of attachment that can be utilized or that may make it harder for outsiders to intervene on behalf of the hostages. (We report more extensively on this aspect of the siege in another paper 17 ).…”
Section: Discussionmentioning
confidence: 98%
“…Subsequent interviews of a sample of 11 hostages found that 10 displayed Stockholm characteristics [16].…”
Section: Complex Ptsd and Appeasementmentioning
confidence: 99%